Anthelmintic resistance to ivermectin and moxidectin in gastrointestinal nematodes of cattle in Europe. Issue 3 (December 2015) - Geurden, Thomas; Chartier, Christophe; Fanke, Jane; di Regalbono, Antonio Frangipane; Traversa, Donato; von Samson-Himmelstjerna, Georg; Demeler, Janina; Vanimisetti, Hima Bindu; Bartram, David J.; Denwood, Matthew J.
Abstract: Anthelmintic resistance has been increasingly reported in cattle worldwide over the last decade, although reports from Europe are more limited. The objective of the present study was to evaluate the efficacy of injectable formulations of ivermectin and moxidectin at 0.2 mg per kg bodyweight against naturally acquired gastro-intestinal nematodes in cattle. A total of 753 animals on 40 farms were enrolled in Germany (12 farms), the UK (10 farms), Italy (10 farms), and France (8 farms). Animals were selected based on pre-treatment faecal egg counts and were allocated to one of the two treatment groups. Each treatment group consisted of between 7 and 10 animals. A post-treatment faecal egg count was performed 14 days (±2 days) after treatment. The observed percentage reduction was calculated for each treatment group based on the arithmetic mean faecal egg count before and after treatment. The resistance status was evaluated based on the reduction in arithmetic mean faecal egg count and both the lower and upper 95% confidence limits. A decreased efficacy was observed in half or more of the farms in Germany, France and the UK. For moxidectin, resistance was confirmed on 3 farms in France, and on 1 farm in Germany and the UK. For ivermectin, resistance was confirmed on 3 farms in the UK, and on 1 farm in Germany and France. The remaining farms with decreased efficacy were classified as having an inconclusive resistance status based on the available data. After treatment Cooperia spp. larvae were most frequently identified, though Ostertagia ostertagi was also found, in particular within the UK and Germany. The present study reports lower than expected efficacy for ivermectin and moxidectin (based on the reduction in egg excretion after treatment) on European cattle farms, with confirmed anthelmintic resistance on 12.5% of the farms. Graphical abstract: Highlights: Multi-centre study in four major cattle markets in Europe. Decreased efficacy in more than half of the farms in three out of four countries. 12.5% of farms with confirmed anthelmintic resistance to ivermectin and moxidectin. Mainly Cooperia larvae found in post-treatment copro-cultures. Also Ostertagia ostertagi larvae found in post-treatment copro-cultures.